2021
DOI: 10.1186/s13048-020-00756-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA FAM83H-AS1 acts as a potential oncogenic driver in human ovarian cancer

Abstract: Objective Ovarian cancer (OC) is one of the most aggressive women cancers with increasing incidence and mortality rates worldwide. Long non-coding RNAs (lncRNAs) could as major players in OC process. Although FAM83H antisense RNA1 (FAM83H-AS1) is demonstrated play an important roles in a many cancers, the detailed function and mechanism has not been reported in OC. Results We integrated multiple kinds of bioinformatics approaches and experiments va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, studies have indicated that m6A modification of lncRNA MIR155HG promotes immune escape of hepatocellular carcinoma cells to upregulate PD-L1 expression [ 33 ]. Similarly, the methylation level of lncRNA FAM83H-AS1 was related to the gene expression of FAM83H-AS1, which was related to immune cell infiltration in OC patients [ 34 ]. These findings further inspired us to conclude that methylation modification of lncRNAs can modulate the immune microenvironment and thus modulate tumor cell biology characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have indicated that m6A modification of lncRNA MIR155HG promotes immune escape of hepatocellular carcinoma cells to upregulate PD-L1 expression [ 33 ]. Similarly, the methylation level of lncRNA FAM83H-AS1 was related to the gene expression of FAM83H-AS1, which was related to immune cell infiltration in OC patients [ 34 ]. These findings further inspired us to conclude that methylation modification of lncRNAs can modulate the immune microenvironment and thus modulate tumor cell biology characteristics.…”
Section: Introductionmentioning
confidence: 99%